STORAGE AND TRANSPORT OF NOBLE GASES IN THE SUBCONTINENTAL LITHOSPHERE - Dunai T.J.; Porcelli D. (My University, 2002)
Characteristics of the upper mantle are typically deduced from mid-ocean and ocean island volcanics that sample the convecting mantle. However, a substantial fraction of the upper mantle is isolated from this convecting reservoir as part of the subcontinental lithosphere. This is a potentially significant reservoir; not only might there be substantial abundances of noble gases and other trace element constituents, but also re-entrainment of this material into the deeper mantle may ultimately impart unique isotopic signatures to mantle domains sampled at ocean islands (McKenzie and O’Nions 1983). The characteristics of the lithosphere can be deduced from magmas derived by melting of this region and from xenolithic materials entrained by rapidly rising magmas. Unfortunately, magmas reaching the surface subaerially are generally strongly degassed and do not retain measurable noble gas concentrations, although some data can be obtained from phenocrysts. In contrast, noble gases as preserved in ultramafic xenoliths from continental volcanic provinces have provided substantial information regarding lithospheric processes and insights into the evolution of the subcontinental mantle. Diamonds also have received considerable attention, with the potential for preserving noble gases from greater depths and considerably longer time periods. Lithospheric mantle samples often show complex histories of metamorphism, deformation, and fluid interaction, and noble gases can provide constraints on the sources of trace element bearing fluids and the evolution of parent-daughter ratios. Noble gases, in particular He, provide distinctive signatures for volatile sources. While the 3He/4He ratio of radiogenic He is very low (~0.01 RA, where RA = 1.4× 10−6, the atmospheric ratio), He found in mid-ocean ridge basalts (MORB) sampling the asthenospheric upper mantle are much higher (~8 RA). This is due to mixing of radiogenic He with He that was trapped within the mantle since Earth formation with ≥120 R …